2008
DOI: 10.1177/1076029608315168
|View full text |Cite
|
Sign up to set email alerts
|

Global Risk Profile Verification in Patients with Venous Thromboembolism (GRIP VTE) in 5 Gulf Countries

Abstract: VTE remains a common problem in medical and surgical patients in the Arabian Gulf states. Recognition of the common risk factors is of extreme importance to implement the appropriate prophylactic strategy according to the published guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…The only study that assessed VTE risk and adequacy of prophylaxis in the Arabian Gulf states (Kuwait, Saudi Arabia, and the UAE) emerged from the global ENDORSE study [23]. However, this study was mainly based on selected surgical and medical patients rather than pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…The only study that assessed VTE risk and adequacy of prophylaxis in the Arabian Gulf states (Kuwait, Saudi Arabia, and the UAE) emerged from the global ENDORSE study [23]. However, this study was mainly based on selected surgical and medical patients rather than pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been performed to assess the independent risk factors for VTE. Different studies showed different independent factors: acute infection, age, cancer, previous VTE [12], immobilization, advanced age, previous VTE, trauma [13], hospital or nursing home confinement, surgery, trauma, cancer with/without chemotherapy, neurological diseases with paresis, central venous catheter or pacemaker, varicose veins, and superficial vein thrombosis [14]. In our study, the independent risk factors were the following: previous VTE, obesity, COPD, heart failure, varicose veins, and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is only one such study [15], which explored VTE risk factors, its rate in surgical and medical wards and the appropriateness of using pharmacologic anticoagulation. This study showed a significant VTE rate in both surgical and medical patients.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed a significant VTE rate in both surgical and medical patients. In addition, there was inappropriate utilization of pharmacologic anticoagulants in patients with established VTE [15]. …”
Section: Introductionmentioning
confidence: 99%